Continuing professional development (CPD): a study on the perception and motives between board of quantity surveyors and their members / Dr Hjh Hamimah Adnan, Nurul Afidaisnaini Janipha, Norfashiha Hashim...[et.al]. - Adnan, Hamimah; Janipha, Nurul Afidaisnaini; Hassan, Fadzil; Ismail, Hafiszah; Hashim, Norfashiha (Institute of Research, Development and Commercialization (IRDC), 2007)
With changes taking place within the construction industry, the quantity surveyor's role has significantly evolved. The Board of Quantity Surveyors (BoQS) Malaysia believes that CPD as one of the fundamental processes to confront this challenge and have made CPD compulsory for all its members. Notwithstanding the numerous provisions and initiatives mooted to encourage BoQS members to participate, there have been critics that suggest the CPD provisions offered have somewhat inadequate and ineffective. It was acknowledged that BoQS and its partner organizations such as the Institution of Surveyors Malaysia and others have considered many options and tried to provide wide ranging activities within the CPD provisions to meet the CPD needs of all their members. However, there is a lack of research to ascertain if this have been successful and there is little data to ascertain the extent to which the CPD offered has been effective. It is recognition for the need to address this that this research was undertaken. It provides a systematic analysis of the response of the members to the CPD initiatives promoted, with view for improvements. The context of the research was developed based on the concepts of education, training, development underpinned by learning. The focus of the investigations was on identifying the how the BoQS members respond to the CPD offered. It emerge the BoQS members generally have a certain preference and reason for their CPD activities. While most agree the need for them to learn and continually improve, in the main, they conceive the CPD offered as primarily a means to fulfill the requirements of their professional membership. This raises some fundamental issues concerning the appreciation of learning from the CPD offered as a means for them improve by learning from these activities. This is discussed at the end of the report together with recommendations for further research.